A case report of successful intraoperative photo- dynamic therapy as the step of combined modality treatment in patient with stage IIIb breast cancer - E. К. Saribekyan; D. D. Pak (Biomedical Photonics, 2013)
The case of successful combined modality treatment in patient with stage IIIB T4bN1M0 breast cancer is reported. The first step included 2 courses of neoadjuvant polychemotherapy in CAF regimen with decrease of tumor size. The second step was irradiation (total dose of 45 Gy) of breast and areas of regional metastasis. The third step was radical mastectomy by Madden with polypositional intraoperative photodynamic therapy with photosens (the output laser power 1500 mW, light dose 30 J/cm2, total time of irradiation – 25.6 min). The histological study of surgical specimen showed infiltrative ductal carcinoma with metastases in 3 nodes without fat invasion. In the post-operative period the patient had 3 courses of adjuvant chemotherapy in CAF regimen. Currently the duration of recurrence-free survival after treatment is 4 years.